An interdisciplinary multi-centered study on the use of enhanced recovery after surgery protocol in colorectal surgery in Türkiye - Ömer Şahin Ilya; Emine Çatal (Asian Journal of Surgery)
Background: This study aims to determine the use of surgical nurses, general surgeons, and anaesthesiologists regarding the implementation of Enhanced Recovery After Surgery (ERAS) protocol in colorectal surgery and the barriers to its implementation. Method: This descriptive study was conducted with three different professionals (surgical nurses, surgeons, anaesthesiologists) in four different hospitals and 268 healthcare professionals who voluntarily participated in the study and had written consent were included in the research sample. Data were collected between March 2020–July 2021 via Personal Information Form and Evaluation Form of ERAS Protocol in Colorectal Surgery. Results: In the study, 57.8 % were nurses, 15.7 % were general surgeons and 26.5 % were anaesthesiologists. It was observed that 73.1 % of the participants hadn’t heard of the ERAS Protocol before, and eight participants who answered the application of the ERAS Protocol steps in colorectal surgery in their clinics answered as ''Yes''. It was determined that very few of the participants correctly knew and/or implemented the recommendations of the ERAS protocol (preoperative, intraoperative and postoperative stages) in colorectal surgery. In addition, the participants reported the obstacles to the implementation of protocol steps as the lack of knowledge (18.1 %), the problems caused by the multidisciplinary work (16.6 %), the resistance to change (12.4 %), and the lack of institutional support (11.4 %). Conclusion: It has been determined that the ERAS Protocol in colorectal surgery is not known enough by health professionals, information and opinions are not compatible with the protocol recommendations, and the barriers to implementation are multifactorial.